Globalisation and international antitrust co-operation - Massimiliano Montini (Fondazione Eni Enrico Mattei (FEEM), 1999)
The globalisation of the world economy on the one side and the expansion of national systems of competition antitrust law on the other side over the last few years have raised to the top of the international agenda the trade and competition issue. While trade barriers are decreasing and business internationalises, cross-border anticompetitive practices increase. Such practices, which may reduce effective competition and undermine the benefits of globalisation, dramatically reveal the limits of an asinchronised international antitrust regime. From one point of view, it is generally very difficult for the panoply of national antitrust systems to tackle domestically cross-border anticompetitive practices, which by their very nature are planned and implemented by several actors under several jurisdictions and have negative effects in many countries. From another point of view, it is generally inefficient for companies operating at the international level to be subject to different national competition rules, due to the lack of common rules at the international level. Up to now, various attempts to synchronise competition principles with a new globalised trading system by establishing a harmonised international competition regime have dramatically failed. Meanwhile, several countries have concentrated their efforts on the development of bilateral co-operation agreements, by their nature more limited in scope. The first part of this paper will be devoted to analyse the main features of the EC-US bilateral co-operation agreements in the field of competition law. On the basis of this analysis, I will argue that although bilateral co-operation must be recognised as an important achievement in the present preliminary stage of the globalisation of the world economy, it should be gradually supplemented, and eventually replaced, by some forms of multilateral antitrust co-operation, possibly within the framework of the WTO. In the second part of this work, I will present some concrete options for the development of multilateral antitrust co-operation in this sense.
Keywords: 330; Konzentrationspolitik; Kartellrecht; Internationale Wirtschaftspolitik; WTO-Regeln; Globalisierung; EU-Staaten; USA; Welt